Incidence of postoperative, major, adverse cardiac events in patients undergoing carotid endarterectomy: A single-center, retrospective study. (January 2022) - Suphathamwit, Aphichat; Leewatchararoongjaroen, Chutima; Rujirachun, Pongprueth; Poopong, Kittipatr; Leesakul, Apichaya; Junyavoraluk, Apichaya; Ruangsetakit, Chanean
Objective: This study aimed to determine the incidence of postoperative major adverse cardiac events for patients undergoing carotid endarterectomy. Methods: This single-center, retrospective study recruited 171 carotid endarterectomy patients between January 1999 and June 2018. Patients who received a carotid endarterectomy in conjunction with other surgery were excluded. The primary outcomes were the incidences of major adverse cardiac events (comprising myocardial infarction, significant arrhythmias, congestive heart failure, and cardiac death) within 7 days, 7–30 days, and > 30 days–1 year, postoperatively. The secondary outcomes were the factors related to major adverse cardiac events and the incidence of postoperative stroke. The patients' charts were reviewed, and direct contact was made with them to obtain information on their status post discharge. Results: The incidences of major adverse cardiac events within 7 days, 7–30 days, and >30 days–1 year of the carotid endarterectomy were 3.5% of patients (95% confidence interval: 0.008–0.063), 1.2% (95% confidence interval: 0.004–0.028), and 1.8% (95% confidence interval: 0.002–0.037), respectively. The major adverse cardiac events occurring within 7 days were arrhythmia (2.3% of patients), cardiac arrest (1.8%), myocardial infarction (1.2%), and congestive heart failure (1.2%), while the corresponding postoperative stroke rate was 4.7%. Conclusion: The 7-day incidence of major adverse cardiac events after the carotid endarterectomy was 3.5%. The most common major adverse cardiac event during that period was cardiac arrhythmia.